Analisis Pendapatan Nasional: Kota Jakarta - Kustiawati, Dedek; Anisa, Anisa; Afiyah Utami, Ersita; Khoirunnisa, Najmina (Jurnal Etnik: Ekonomi-Teknik, 2023)
This paper aims s to determine the gross national income and economic growth in the capital, namely the city of Jakarta. This study uses a quantitative approach. This study also identifies the impact of the corona virus that has occurred for two years on the gross national income of the City of Jakarta. The results of the study show that the gross national income of the City of Jakarta has grown quite significantly from year to year. Despite the Corona outbreak and with the increase in the census of the poor and the population of the City of Jakarta, this is not a barrier to increasing the amount of the Regional Budget for the City of Jakarta. Regional revenues for the City of Jakarta have grown significantly from year to year. Pemprov DKI Jakarta must continue to work hard to stabilize and further improve the safety level of the City of Jakarta PPE for the remainder of the year while continuing to consider what, if anything, has the potential to undermine this upward trend. Therefore, accelerating PPE in Jakarta will have a negative impact on economic growth and the local population's sense of security.